2012
DOI: 10.1016/j.bpj.2012.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Curli A Production on Living Bacterial Surfaces by Scanning Probe Microscopy

Abstract: Curli are adhesive surface fibers produced by many Enterobacteriaceae, such as Escherichia coli and Salmonella enterica. They are implicated in bacterial attachment and invasion to epithelial cells. In this study, atomic force microscopy was used to determine the effects of curli on topology and mechanical properties of live E. coli cells. Young's moduli of both curli-deficient and curli-overproducing mutants were significantly lower than that of their wild-type (WT) strain, while decay lengths of the former s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 32 publications
4
17
1
Order By: Relevance
“…Our results showed that OmpR and CsgD do affect the mechanical properties of the cells outer surface; the much lower E and P0 of expressing curli (E. coli PHL 628 and E. coli MG1655 pT7-7CsgD) is probably the result of the increased need to excrete the curli subunits CsgA and CsgB or through the role of CsgD in the regulation of cellulose production 12,47,48 . The values of Young modulus (E) for E. coli MG1655 obtained in this work ( Figure 5) were similar to those presented by Oh et al 49 and Chen et al 50 for other strains of E. coli. In general, surface distribution of E is assumed to follow a Gaussian profile 35 , whilst not normal distribution for adhesion force and curli geometrical parameters have been reported 40,41 .…”
Section: Discussionsupporting
confidence: 90%
“…Our results showed that OmpR and CsgD do affect the mechanical properties of the cells outer surface; the much lower E and P0 of expressing curli (E. coli PHL 628 and E. coli MG1655 pT7-7CsgD) is probably the result of the increased need to excrete the curli subunits CsgA and CsgB or through the role of CsgD in the regulation of cellulose production 12,47,48 . The values of Young modulus (E) for E. coli MG1655 obtained in this work ( Figure 5) were similar to those presented by Oh et al 49 and Chen et al 50 for other strains of E. coli. In general, surface distribution of E is assumed to follow a Gaussian profile 35 , whilst not normal distribution for adhesion force and curli geometrical parameters have been reported 40,41 .…”
Section: Discussionsupporting
confidence: 90%
“…Curli fiber equilibrium lengths on E. coli were reported to be 137-373 nm. 17 The equilibrium length of proteinaceous fimbriae on E. coli ranged from 125-272 nm. 26 -comparable to the values measured for the wild-type strain of P. fluorescens, and the lapA and lapB mutants (∼120 nm).…”
Section: Polymer Conformation On the Surface Of P Fluorescensmentioning
confidence: 99%
“…Steric models of the form developed by Alexander-de Gennes (A-dG model) have been used to characterize molecules on bacterial surfaces including lipopolysaccharides (LPS), extracellular polymeric substances, and surface polymers. [16][17][18] Therefore, the objective of this study was to apply the steric model to AFM data, and characterize the physical characteristics of the LapA protein of P. fluorescens.…”
Section: Introductionmentioning
confidence: 99%
“…Studies with varying curli production indicate that the fibers are critical for strong adhesion ( 34 , 45 ), and increased curli expression has been shown to result in pellicles with increased surface elasticity and strength ( 43 ). Curli overproduction has been shown to substantially increase adhesion, and attachment strength has been noted to vary by surface type: the strongest interactions were seen for hydrophobic plastics, relative to hydrophilic metals or glass ( 45 , 46 ). Still, the fundamental mechanisms that allow curliated biofilms to achieve this outstanding adhesion are yet unknown.…”
Section: Introductionmentioning
confidence: 99%